Acid Mine Drainage Treatment at Herbert Stream, Stockton - P Lindsay; M Watts (The Australasian Institute of Mining and Metallurgy, 2007)
Herbert Stream, a tributary of the Waimangaroa River on the Stockton Plateau, has elevated metal concentrations and low pH characteristic of acid mine drainage (AMD). Dissolved aluminium concentrations average 8.3 ppm, iron 1.4 ppm, manganese 0.69 ppm, and zinc 0.12 ppm and pH ranges from 2.8 to 3.2. Flow rates range from 2.3 to 26.6 L/s with an average of 5.3 L/s. To determine the effectiveness of different treatment strategies, a small amount of the AMD was diverted through three small-scale passive AMD remediation systems over an eight month period. These included a reducing and alkalinity producing system (RAPS), a limestone leaching bed (LLB), and an open limestone channel (OLC). Both the RAPS and the LLB performed well, effectively removing metals and restoring pH. The RAPS lowered aluminium concentrations by up to 99%, iron 97%, manganese 95%, and zinc 80% and the LLB lowered aluminium concentrations by up to 99%, iron 99%, manganese 92%, and zinc 91%. The pH was restored to between 6.4 and 7.4 by the RAPS and to between 7.3 and 7.9 by the LLB. The OLC performed well as long as the residence time was similar to that of the other treatment systems. OLC removal rates for aluminium was up to 99%, iron 94%, and manganese 21%, and the pH was restored up to 5.6. Due to its simplicity and effectiveness, it is proposed the LLB be constructed to fullscale size to treat the entire Herbert Stream.